2019
DOI: 10.1002/ieam.4196
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic Factors Influence Surface Water Herbicide Concentrations Following Silvicultural Aerial Application in Oregon's North Coast Range

Abstract: Nontarget impacts of routine aerial silvicultural practices on surface water quality are not well documented. Thus, uncertainty remains regarding herbicide treatment effects on ecological and human health. To investigate factors that influence silvicultural herbicide concentrations in surface water and identify any potential risks, we conducted a 2‐year study that monitored multiple streams for herbicide residues following aerial application of glyphosate, clopyralid, sulfometuron methyl (SMM), and metsulfuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…This relationship indicates a plausible connection between cumulative effects of herbicide applications within a catchment basin and the type and amount of chemical exposure to downstream organisms. However, previous BMP research has highlighted the role of variable abiotic factors, which were not controlled in our study, in understanding offsite movement of chemicals [ 67 , 68 ]. Caldwell and Courter (2020) found that proximity to herbicide application sites followed by rainfall had the greatest influence on herbicide concentration in downstream Oregon coastal waters [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This relationship indicates a plausible connection between cumulative effects of herbicide applications within a catchment basin and the type and amount of chemical exposure to downstream organisms. However, previous BMP research has highlighted the role of variable abiotic factors, which were not controlled in our study, in understanding offsite movement of chemicals [ 67 , 68 ]. Caldwell and Courter (2020) found that proximity to herbicide application sites followed by rainfall had the greatest influence on herbicide concentration in downstream Oregon coastal waters [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous BMP research has highlighted the role of variable abiotic factors, which were not controlled in our study, in understanding offsite movement of chemicals [ 67 , 68 ]. Caldwell and Courter (2020) found that proximity to herbicide application sites followed by rainfall had the greatest influence on herbicide concentration in downstream Oregon coastal waters [ 67 ]. Our findings are consistent with these studies and indicate that a rainfall event may result in higher herbicide concentrations in areas with more herbicide applications upstream.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation